The burden of HDV infection: A ten-years' experience of a sicilian tertiary centre of liver disease. (March 2023) - Rizzo, G.E.M.; Ferraro, D.; Rancatore, G.; Graceffa, P.; Falco, G.; La Mantia, C.; Calvaruso, V.; Di Marco, V.
Abstract : Introduction: Hepatitis B virus (HBV) and Hepatitis D virus (HDV) super-infection is considered as one of the most dangerous forms of chronic viral hepatitis, but the burden of the HDV infection worldwide could be underestimated. The aim of our study is to evaluate the burden of HDV among a cohort of HBV patients with a long-term follow-up (more than 10 years). Methods: This retrospective study enrolled HBV patients from a tertiary liver centre between 1998 and 2022. We performed screening for HDV including anti-HDV antibodies at baseline and during the last year of follow-up. We estimated the prevalence of HDV infection among those patients with HBsAg positivity. Disease outcomes as progression to advanced liver disease, decompensation of liver cirrhosis, development of hepatocellular carcinoma (HCC), portal thrombosis or death were collected and estimated using Kaplan-meier curves. Results: We evaluated a total of 616 HBsAg positive patients who attended our liver tertiary (78% males; mean age 62 years). At the end of our retrospective analysis, we identified 52 patients (8.4%) with HBV / HDV coinfection Of these forty-two were italians (80%) while ten (20%) were foreigners9 of 10 of the foreigners patients10 were Romanians. At baseline, 3 of 52 HBV-HDV coinfected patients had a chronic asymptomatic infection (5.7%), 14 had a chronic hepatitis (26.9%) and 35 had a liver cirrhosis (67.3%). In the subgroup of 35 cirrhotic patients, 19 patients (54.2%) developed at least decompensation of their iver disease and 13 patients (37.1%) developed HCC. Overall, 15 patients (28.9%) died during a mean follow up of 115 months. Discussion: Our retrospective study confirms that HBV / HDV coinfection is still widespread in cohorts of patients with chronic HBV infection and that it results in severe liver disease with a high risk of developing heart failure, HCC and death.